Management of Hylesia nanus (Lepidoptera: Saturniidae) on Eucalyptus (Myrtaceae) plantations - Masson, Marcus V.; Tavares, Wagner de S.; Pereira, Deivide W. V.; Matos, William C.; Lopes, Fabricio de A.; Ferreira-Filho, Pedro J.; Wilcken, Carlos F. [UNESP]; Zanuncio, Jose C. (Florida Entomological Soc, 2017)
The management of Hylesia nanus Walker (Lepidoptera: Saturniidae), a defoliator of Eucalyptus species (Myrtales: Myrtaceae), was evaluated on the northern coast of Bahia State, Brazil, by performing 3 connected experiments: (1) monitoring of H. nanus moths by using light traps; (2) biological control of H. nanus pupae by releasing the endoparasitoid Palmistichus elaeisis Delvare & La Salle (Hymenoptera: Eulophidae); and (3) chemical control of H. nanus larvae with 1 spraying of bifenthrin + etilenoxi. The light traps effectively assisted the monitoring and control of H. nanus moths, with a mean population peak (+/- SE) of 801 +/- 438 individuals collected per trap in a 23 d nocturnal period. Palmistichus elaeisis was recovered from the H. nanus pupae 96 h post release, with a parasitism rate of 23 +/- 3%, indicating an ability to parasitize and contribute to insect suppression. Release of this parasitoid can be integrated with monitoring using light traps. Chemical control was highly effective against the last instar H. nanus larvae, with only 11 +/- 3 larval survivors per tree trunk 24 h post spraying. Thus, the monitoring of moths by using light traps, control of pupae by releasing P. elaeisis, and chemical control of last instar larvae are methods that could be integrated into a management plan for H. nanus.
Keywords: chemical control; light trap; Palmistichus elaeisis; Tachinidae